2008
DOI: 10.1017/s1368980007001085
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc deficiencies in China: what is a feasible and cost-effective strategy?

Abstract: In order to prioritise interventions for micronutrient deficiencies in China, the populations affected by iron and zinc deficiencies were assessed based on data from the 2002 China National Nutrition and Health Survey. The costs and costeffectiveness of supplementation, food diversification and food fortification were estimated using the standard World Health Organization ingredients approach. Results indicated that 30% of children (,2 years), adults (.60 years), pregnant and lactating women, and 20% of women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 41 publications
5
126
1
2
Order By: Relevance
“…Zinc biofortified rice and wheat may reduce this burden by 20%-51% and save 0.6-1.4 million DALYs each year. The costs for saving one DALY through crop biofortification amount to US$ 0.73-7.31, which is very cost-effective and lower than that of most other micronutrient interventions (Stein 2006;Ma et al 2007). More recently, Meenakshi et al (2010) concluded that overall, biofortification can make a significant impact on reducing the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner; however, the impacts differ depending on the combination of crop, micronutrient and country, and the major reasons underlying these differences are identified to inform policy.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc biofortified rice and wheat may reduce this burden by 20%-51% and save 0.6-1.4 million DALYs each year. The costs for saving one DALY through crop biofortification amount to US$ 0.73-7.31, which is very cost-effective and lower than that of most other micronutrient interventions (Stein 2006;Ma et al 2007). More recently, Meenakshi et al (2010) concluded that overall, biofortification can make a significant impact on reducing the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner; however, the impacts differ depending on the combination of crop, micronutrient and country, and the major reasons underlying these differences are identified to inform policy.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no evidence of the health impact to tackle folate deficiency through biofortification, or the burden of folate deficiency. Despite China's support for GM technology and biofortification (Campos-Bowers and Wittenmyer, 2007)(see section 2.5), China is a relatively new area to conduct health impact studies on biofortified staple crops (Ma et al, 2007;Fan et al, 2009). At present, no (health impact) studies focused on GM biofortification in China.…”
Section: The Health Impact Of Interventionsmentioning
confidence: 99%
“…With respect to zinc deficiency, estimates of people with an inadequate intake of zinc vary between 86 (Ma et al, 2007) and 183 million (Micronutrient Initiative, 2009). …”
Section: Folate Deficiency Compared With Other Micronutritional Deficmentioning
confidence: 99%
See 2 more Smart Citations